Investigation of Surrounding Rock and Pipe Lining Structural Response Characteristics in Steep Slope Tunnels - Junling Qiu; guanfei Yang; xiaolong Huang; hu Luo; gang Si; haoran Hu; yuhua Chen (Electronic Journal of Structural Engineering, 2024)
To provide reference and guidance for ensuring the safe construction of tunnel construction,taking a mountain road tunnel project as the background,the finite element numerical simulation method is used to study the excavation of large longitudinal slope tunnel by TBM method.The vertical displacement of surrounding rock shows the deformation trend of vault subsidence and arch bottom uplift,and the peak value of lateral displacement decreases gradually with the increase of longitudinal slope gradient.The segment at the vault and arch bottom of the tunnel are subjected to positive bending moment,and the spandrel arch waist and arch foot are subjected to negative bending moment.The maximum value of the absolute value of the axial force is located at the arch waist.In addition,the deformation characteristics of the surrounding rock and the stress characteristics of the segment during the tunnel crossing the fault fracture zone are analyzed.The research shows that the vertical displacement of the surrounding rock is significantly larger than that of the intact stratum,and the closer to the fault fracture zone,the larger the vertical deformation is,and the closer to the tunnel entrance section,the larger the uplift deformation is.The horizontal displacement of the surrounding rock is obviously smaller before it enters the fault fracture zone,and the displacement increases rapidly when it is constructed to the fault range,and reaches the peak at the center of the fault.After crossing the fault,the displacement changes little.